Synthetic precursor to vertical TiO2 nanowires - Mishra, Biswajit; Ghildiyal, P.; Agarkar, Shruti A.; Khushalani, Deepa (Materials Research Express, 2014)
An easy protocol for improvement in formation of the photoanode in a dye sensitized solar cell is addressed. Specifically, a novel synthesis for the formation of a TiO2 precursor: titanium butanediolate, is detailed. This precursor is found to have higher thermal and temporal stability than commercially available TiO2 precursors and it has successfully been employed in the one-pot synthesis of rutile nanowires grown directly on a conducting substrate: fluorine doped tin oxide (FTO). This synthesis has been further extended to directly form a mixed phase TiO2 film consisting of rutile nanowires along with anatase spherical particles on FTO and this assembly has been used as the photoanode in a dye-sensitized solar cell. The synergistic effect of the two phases has provided a net DSSC efficiency of 4.61% with FF = 61%.
Keywords: Nanomaterials; Nanowires; TiO2